Cytotoxicity study of selected ethnomedicinal plants used by Dumagats in Barangay San Lorenzo, Norzagaray and Kabayunan, Doña Remedios Trinidad, Bulacan - Domingo, Mark Lloyd M., Gabales, Matthew, Guerra, Dominique Ann A., Lindo, Jacinta Sophia Reign M. 4 0 16; 5
ABSTRACT: Many indigenous tribes do not have access to modern medicine, and for this reason they use ethnomedicinal plants, which are used to address several medical ailments. The risks to ethnomedicinal knowledge and practices in the Philippines, as well as the lack of information on traditional medicine, increase the risk of indigenous people being unaware of the potentially harmful and/or fatal cytotoxic activity of the plants. The present study was conducted to provide documentation of the ethnomedicinal knowledge and practice of Dumagats in Barangays San Lorenzo and San Mateo, Norzagaray, Bulacan. This study also determines the cytotoxicity of three selected common medicinal plants, Artemisia vulgaris, Blumea balsamifera, and Coleus amboinicus. The three were selected and subjected to crude ethanolic leaf extraction. Extracts were then investigated for cytotoxicity potential using brine shrimp lethality assay and trypan blue assay. A total of 22 ethnomedicinal plants were used to treat common ailments. The most commonly used plant parts are the leaves, and these ethnomedicinal plants were often decocted and taken orally. A. vulgaris, B. balsamifera, S. spontaneum, and D. philippinensis were the most used plants in the barangays, with a use value of 0.57. Exposure of S. cerevisiae S-04 strain to A. vulgaris, C. amboinicus, and B. balsamifera extracts at varying concentrations and durations revealed distinct cytotoxic effects. At higher concentrations, significant decreases in cell viability were observed over time, indicating concentration-dependent cytotoxicity. Conversely, lower concentrations exhibited minimal cytotoxic effects. Prolonged exposure exacerbated cytotoxicity, suggesting time-dependent effects. These findings highlight the concentration- and time-dependent cytotoxic effects of plant extracts on yeast cells. Overall, this research emphasizes the significance of documenting ethnomedicinal practices and assessing the cytotoxicity of medicinal plants, shedding light on their varying effects over time and concentration, crucial for understanding their potential impact on health.
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2